As doses da literatura pós-colonial moçambicana: um olhar sobre a linguagem, a representação e o trágico em Venenos de Deus, Remédios do diabo, de Mia Couto - Zanutim, Lorraine (2016)
This study which its focus is the Veneno de Deus, Remédios do diabo’s literary narrative approach of the Mozambican author Mia Couto intends to demonstrate the way the author works with the articulation between the Mozambican post-colonial period and its consequences to the colonized people such as the search for their indentities. The novel establishes itself like an adequate model to represent the human dramas by allowing every type of language and hybridisms. Thus, by the race’s drama of the Mozambican people, the author looks for ways to connect the past and the present, fusing them in a possible integrated future. It can be observed in Mia Couto’s productions a language work referring to the oral narratives by the creation and transcription of the proverbs and maxims, besides a watchful look into the characters’ memories, crucial element to the post-colonial resumption and to the understanding of a indentitary project search. It can also be invetigated the tragic elements in the book which are consequences of an articulated plot between the characters. Therefore, the theoretical basis will be accomplished from Ernst Cassirer, Ana Malfalda Leite, Walter Benjamin, Ángel Rama, Stuart Hall, Fernando Ortíz and others’ theories.